Nation and family : personal law, cultural pluralism, and gendered citizenship in India - Subramanian, Narendra (Stanford : Stanford University Press, 2014)
The distinct personal laws that govern the principal religious groups are a major aspect of Indian multiculturalism and secularism, and support specific gendered rights in family life. This is the most comprehensive study of the public discourses, processes of social mobilization, legislation, and case law that formed India's three major personal-law systems, which govern the Hindus, the Muslims, and the Christians. It is the first to systematically compare Indian experiences to those in various other countries that inherited personal laws specific to religious group, sect, or ethnic group.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 3, 2014).
Keywords: Domestic relations -- India; Families -- Political aspects -- India; Women -- Legal status, laws, etc. -- India; Religious minorities -- Legal status, laws, etc. -- India; Law reform -- India -- History; Culture and law -- India; Multiculturalism -- India; Nationalism -- India; Law; Politics & government; Comparative law; Law & society, gender issues